Implementation of The Thematic-Integrative Learning to Enhance Students Skill in The 4.0 Era - Qiqi Yuliati Zaqiah; Yeti Heryati; Ibrahem Narongraksakhet (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
This research aims to describe the design of thematic-integrative learning model, its implementation in the learning process, the influence of the model on enhancing students' 4C's skill (Communication, Cooperative, Critical thinking, Creativity), and the analysis of the supporting hindering factors that may affect the implementation of the learning model. The research utilized a qualitative approach with a descriptive analytics method. This study collected its data through an interview, observation, and documentation. The result reveals that thematic-integrative learning can increase students' ability in the era of 4.0. The outcome is demonstrated by students' competency in formulating a project and its report. Thus, it is shown that students' capability in using technology, collaboration, written and spoken communication, self-management, critical and creative thinking, and problem-solving can be sharpened. Moreover, the supporting factors found in this research are a competent teacher, learning curriculum, active students, school facilities and expenses. On the other hand, the factors that may hinder the implementation are the disparity of the teachers' proficiency, the integration of curriculum, which is often inaccurate, students' unique character and capability, facilities that are not yet optimal, and an extensive cost for projects and performances.